The effects of circuit exercise training strategy on health-related physical fitness level and biomarkers in elderly people with cardiovascular diseases - Boudehri, Mohamed El amine; Belkadi, Adel; Dahoune, Oumri; Atallah, Ahmed (Quality in Sport, 2023)
This study investigated the effects of a 12-week circuit exercise training intervention on health-related physical fitness and biomarkers in elderly adults with cardiovascular diseases. A total of 69 participants underwent the circuit exercise training program, which included stretching, aerobic activity, and weight training. The results showed that the participants had improved performance in cardiovascular and strength tests, with grip and back muscle strength showing improvement. However, sit-ups were lower than the average, and power, reaction time, and agility needed more effort. The high sensitivity C-reactive protein value reached a medium infection risk level for cardiovascular illnesses. The study concluded that there was a strong association between health-related physical fitness and biomarker index in senior persons with a medium risk cluster of cardiovascular illnesses. The study also found that BMI correlated positively with biomarker index, while cardiovascular fitness, agility, and flexibility correlated negatively with biomarker index.